Seismic performance of timber through-tenon joints with shrinkage flaw in tenon - Li, Shengcai; Li, Da; Chen, Tao; Milani, Gabriele; Shi, Shengxiang; Wang, Shuqiang (Journal of Building Engineering, 2023)
In several Chinese historic timber buildings, widening flaws in tenon of joints are usually a consequence of weathering and shrinkage. To investigate the impact of flaws on the seismic performance of through-tenon joints (TTJ), cyclic loading tests on four specimens were conducted. The hysteresis, skeleton, energy dissipation and stiffness experimental curves were so obtained. A finite element (FE) model to describe the behavior of such experimental specimens has been then established calibrating the mechanical properties by means of coupon tests. By comparing the numerical simulation results with the experimental results, it is concluded that this kind of damage has less impact on the mechanical performance of TTJs under negative load, while it has a greater impact under positive load. The impact was more noticeable as the length of large head of through tenon increased. The rotation capacity, stiffness and energy dissipation capacity of the damaged joints were significantly lower than the intact ones. The bearing capacity of TTJs with the damage decreased by about 32.4%–38.5%, the energy dissipation coefficient decreased by about 17%–38%, and the cumulative energy consumption decreased by 33.3%–60%. •Seismic performance of timber through-tenon joints TTJs with shrinkage flaw in tenon.•Experimental cyclic loading tests on four specimens.•Hysteresis, skeleton, energy dissipation and stiffness experimental evaluation.•Advanced FE model in Abaqus to confirm experimental results.•Damage has great impact under positive load (bearing capacity decrease of 32.4% ∼ 38.5%).